PENYELESAIAN SENGKETA KONSUMEN DALAM TRANSAKSI CROSS BORDER E-COMMERCE SEBAGAI UPAYA MEMBERIKAN PERLINDUNGAN HUKUM - Firmansyah Umar; Fenty U. Puluhulawa; Fence M. Wantu (The Juris, 2023)
This article aims to know the consumer protection in transactioncross border e-commerceand consumer dispute resolution due to losses experienced by consumers in the transaction. This research is a normative legal research that uses secondary data such as legislation. Legal protection of consumers in transactions e-commerceis regulated by Law No. 8 of 1999 on Consumer Protection and Law No. 19 of 2016 on Amendments to Law No. 11 of 2008 on Electronic Information and Transactions. Zincleta settlement in cross border e-commerceinvolves various problems, especially related to standard clauses referring to foreign jurisdictions. The ITE Law provides a legal basis for e-commerce,but does not specifically regulate cross-border agreements, various methods of dispute resolution, such as mediation, arbitration, and ODR (Online Dispute Resolution) becomes relevant in this context. In conclusion, legal protection of consumers in cross-border e-commerceneeds to be strengthened. Dispute resolution involves the role of institutions such as the Consumer Dispute Resolution Agency (BPSK) and the Indonesian National Arbitration Board (BANI), but the implementation of ODR can be an innovative solution to handle disputes efficiently, especially in the international sphere.need to be strengthened.